Correction to: Sargramostim to treat patients with acute hypoxic respiratory failure due to COVID-19 (SARPAC): A structured summary of a study protocol for a randomised controlled trial - Cedric Bosteels; Bastiaan Maes; Karel Van Damme; Elisabeth De Leeuw; Jozefien Declercq; Anja Delporte; Bénédicte Demeyere; Stéfanie Vermeersch; Marnik Vuylsteke; Joren Willaert; Laura Bollé; Yuri Vanbiervliet; et al. (Trials, 2020)
An amendment to this paper has been published and can be accessed via the original article.